Medición de brechas del registro único de contribuyentes (R.U.C) en la provincia del Carchi - Rojas Rosero, Anita Yadira (2015)
in the province of Carchi has seen the need to establish control taxpayers regarding compliance with tax obligations, looking exactly the number of taxpayers who have adequate control of their activities as well as determine the percentage of taxpayers somehow elude Or evade their tax by nol enrolling in the National Register of Taxpayers obligations. It is for these reasons that created the need for this thesis topic, should determine whal are the main causes that motivates evasion and to measure the gap in enrollment. For the presentation of the research project has been used qualitative and guantitative modality, as well as theoretical and empirical research methods, techniques used are 318 to 1 interview SuIvey which were necessary to diagnose the factors that insidien in non-registration the RUC. The line of research on the subject regulations and accounting methodology focuses. In the proposal ine registration gap of 69% and a level of breach of 74,91%, which was calculated based on data obtained in the workup is determined.